Comparison of pellicle and shake flask-grown BCG strains by quality control assays and protection studies. (January 2019) - Fitzpatrick, Megan; Ho, Mei Mei; Clark, Simon; Dagg, Belinda; Khatri, Bhagwati; Lanni, Faye; Williams, Ann; Brennan, Michael; Laddy, Dominick; Walker, Barry
Abstract: A global BCG vaccine shortage began in 2013 which impacted availability for infant vaccinations, as well as preclinical studies and clinical trials of new TB vaccines. Stakeholders met in 2015 at McGill University in Montreal to discuss the shortage and potential mitigation strategies. Manufacturing BCG through a more tractable liquid fermentation process instead of the traditional pellicle growth method was considered a potentially viable strategy. This pilot program compared pellicle-grown and shake flask-grown BCG strains (as a first step towards modeling fermenter-produced BCG vaccine) in selected quality control assays, as well as mouse and guinea pig protection studies. Conventional pellicle-grown, lyophilized BCG WHO Reference Reagents (Danish, Moreau, Russian, Tokyo strains) were obtained from the National Institute for Biological Standards and Control (NIBSC), UK. Strains were grown in shake flasks and glycerol stocks prepared. Shake flask-grown BCG culture preparations generally met the requirements of quality control testing at NIBSC. In mouse and guinea pig protection studies there were no significant differences in lung colony forming units (CFUs) between shake flask-grown and pellicle-grown preparations, with the exception of BCG Russian, where the shake flask-grown preparation protected better in mice ( P  = 0.0042), but the pellicle-grown preparation protected better in guinea pigs ( P  = 0.0015). Producing BCG vaccines by a more tractable liquid growth process could be a viable solution to the global BCG shortage.